2018
DOI: 10.1007/s11845-018-1871-5
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in the Emergency Department hospital staff at Cork University Hospital

Abstract: Burnout is very common in the Emergency Department at CUH. Approximately three out of four staff met the cutoff for burnout. Self-reported depression was also significantly associated with burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 18 publications
2
22
0
2
Order By: Relevance
“…High levels of stress are not uncommon in healthcare workers, but likely exacerbated in the wake of a global pandemic of a new infectious disease with information and control strategies continuously changing. Previous work reported high burnout rates of a small sample of radiographers in Ireland [18] and coupled with the considerable number of radiographer respondents in this work (30%) considering leaving their job or retiring since the COVID-19 outbreak, should be a concern for management and the profession alike. The potential exists for long-term negative effects on the current workforce [19] which may impact on services nationally unless stress and burnout among this profession are specifically addressed post pandemic.…”
Section: Discussionmentioning
confidence: 77%
“…High levels of stress are not uncommon in healthcare workers, but likely exacerbated in the wake of a global pandemic of a new infectious disease with information and control strategies continuously changing. Previous work reported high burnout rates of a small sample of radiographers in Ireland [18] and coupled with the considerable number of radiographer respondents in this work (30%) considering leaving their job or retiring since the COVID-19 outbreak, should be a concern for management and the profession alike. The potential exists for long-term negative effects on the current workforce [19] which may impact on services nationally unless stress and burnout among this profession are specifically addressed post pandemic.…”
Section: Discussionmentioning
confidence: 77%
“…This was consistent with other studies in terms of prevalence, however, other studies showed female staff suffered from higher work-related burnout rather than personal burnout. 51,52 Furthermore, age and marital status did not have signi cant correlations with burnout or stress. The data also re ected that Bahraini EPs were experiencing higher personal burnout, work-related burnout stress overload, personal vulnerability, and event load in contrast to their non-Bahraini colleagues (p< 0.05; see Table 7).…”
Section: Discussionmentioning
confidence: 87%
“…During a crisis, such as the current COVID-19 pandemic, these challenges can substantially increase. Healthcare workers are routinely subjected to intense stimuli in their work that may lead to burnout (Chernoff et al 2018) and result in distress and emotional suffering (Ducar et al 2020). In this current unprecedented global pandemic, front-line healthcare workers are risking their lives in the line of duty requiring them to demonstrate courage in the presence of fear.…”
Section: Introductionmentioning
confidence: 99%